THE EFFECTS OF ORGANIZING CHEMISTRY LESSONS BASED ON THE FINNISH EDUCATIONAL SYSTEM IN GENERAL SCHOOLS OF UZBEKISTAN ("XXI ASRDA INNOVATSION TEXNOLOGIYALAR, FAN VA TAʼLIM TARAQQIYOTIDAGI DOLZARB MUAMMOLAR" nomli respublika ilmiy-amaliy konferensiyasi, 2024)
This study investigates the effects of implementing chemistry lessons inspired by the Finnish educational system in general schools across Uzbekistan. Drawing upon the renowned Finnish approach to education, which emphasizes student-centered learning, inquiry-based instruction, and collaborative problem-solving, this research explores the potential benefits and challenges of adopting similar practices in the context of chemistry education in Uzbekistan. Through a mixed-methods approach, including quantitative assessment of academic achievement and qualitative exploration of teacher and student experiences, this study examines the impact of Finnish-inspired chemistry lessons on student engagement, conceptual understanding, and critical thinking skills. Findings reveal notable improvements in student outcomes, indicating enhanced enthusiasm for learning, deeper conceptual comprehension, and increased motivation to pursue further studies in chemistry. Additionally, qualitative insights provide valuable perspectives on the cultural adaptation of Finnish educational models within Uzbekistan's educational framework. This research contributes to the ongoing dialogue on educational reform by highlighting the potential of cross-cultural exchange and innovation in enhancing chemistry education in diverse global contexts.